A review on purposes of project manager’s leadership skills in pre-construction phase of sustainable construction projects - Noorul Adharina Zulkiffli,; Aryani Ahmad Latiffi, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Project manager has an important role as a leader in sustainable construction project by implementing sustainability concept into practices. Considering the responsibilities of project manager, their role is noticeable in achieving sustainability objectives in a project. However, a failure to manage a project especially at pre-construction phase in sustainable construction can cause conflicts that can lead to project delay. The ability of project manager as a leader is crucial to manage a project in the early phase. Yet, this requires project manager as a project leader to have effective leadership skills to manage pre-construction phase of sustainable construction projects due to the management commitment towards sustainability. Thus, the aim this paper is to identify the purposes of project manager’s leadership skills in pre-construction phase of sustainable construction projects. The overall intent of this paper is to highlight the purposes and identify project manager’s leadership skills in pre-construction phase of sustainable construction projects so it can be adapted in current practices, hence, to effectively manage the sustainable construction projects strategically.